Low Copy Numbers of DC‐SIGN in Cell Membrane Microdomains: Implications for Structure and Function. (3rd December 2013) - Liu, Ping; Wang, Xiang; Itano, Michelle S.; Neumann, Aaron K.; de Silva, Aravinda M.; Jacobson, Ken; Thompson, Nancy L.
Abstract Presently, there are few estimates of the number of molecules occupying membrane domains. Using a total internal reflection fluorescence microscopy (TIRFM) imaging approach, based on comparing the intensities of fluorescently labeled microdomains with those of single fluorophores, we measured the occupancy of DC‐SIGN, a C‐type lectin, in membrane microdomains. DC‐SIGN or its mutants were labeled with primary monoclonal antibodies (mAbs) in either dendritic cells (DCs) or NIH3T3 cells, or expressed as GFP fusions in NIH3T3 cells. The number of DC‐SIGN molecules per microdomain ranges from only a few to over 20, while microdomain dimensions range from the diffraction limit to > 1 µm. The largest fraction of microdomains, appearing at the diffraction limit, in either immature DCs or 3 T3 cells contains only 4–8 molecules of DC‐SIGN, consistent with our preliminary super‐resolution Blink microscopy estimates. We further show that these small assemblies are sufficient to bind and efficiently internalize a small (∼50 nm) pathogen, dengue virus, leading to infection of host cells. <inline-graphic xlink:href="ark:/27927/pgg409t86xq" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />